Trehalose Activates CRE-Dependent Transcriptional Signaling in HT22 Mouse Hippocampal Neuronal Cells: A Central Role for PKA Without cAMP Elevation - Maronde, Erik (Frontiers in Molecular Neuroscience, 2018)
Cyclic adenosine 3`,5`-monophosphate (cAMP) regulated element binding protein (CREB) is a transcription factor involved in many different signaling processes including memory storage and retrieval. The mouse hippocampal neuronal cell line HT22 is widely used as a model system for neuronal cell death and cellular signal pathway investigations. For the present work a variant of HT22 cells with a stably expressed CRE-luciferase reporter (HT22CRE) is introduced, characterized and used to investigate cAMP-dependent and independent cAMP regulated element (CRE)-dependent signal processes. Trehalose (Mykose or 1-α-Glucopyranosyl-1-α-glucopyranoside) is a naturally occurring disaccharide consisting of two α, α`,1,1-glycosidic connected glucose molecules which is present in a wide range of organisms but usually not found in mammals. Trehalose has been shown to activate autophagy, a process which regulates the degradation and recycling of proteins and organelles. The exact processes how trehalose application works on mammalian neuronal cells is not yet understood. The present work shows that trehalose application dose-dependently elevates CRE-luciferase activity in HT22 cells and acts synergistically with cAMP-elevating agents. In this pathway PKA appears to be the most important factor and the stress kinase p38 and protein tyrosine kinases (PTKs) act as modulators.